Pengaruh Konten Visual dan Interaksi Media Sosial terhadap Minat Beli Kuliner Lokal Batam - Ria Pratiwi; Heri Nuryanto; Tirta Mulyadi; Agung Arif Gunawan (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to determine the effect of visual content and social media interaction on consumer purchasing interest in local culinary products on Instagram and TikTok platforms in Batam City. This study uses an associative quantitative approach with a survey method. Data was obtained by distributing questionnaires to respondents who are active users of Instagram and TikTok who have seen or interacted with local culinary content in Batam City. The data analysis techniques used included validity and reliability tests, classical assumption tests, and multiple linear regression, with a sample size of 100 people. The results showed that visual content and social media interaction had a positive and significant effect on consumer purchasing interest. Simultaneously, these two variables were able to explain 55.9% of the variation in purchase interest, while the remaining 44.1% was influenced by other factors such as price, product quality, promotion, and brand image. These findings indicate that social media-based marketing strategies with attractive visual content and active interaction can increase consumer purchase interest in local culinary products, especially among young social media users.